1979
DOI: 10.1042/bj1790561
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans of the intervertebral disc. Homology of structure with laryngeal proteoglycans

Abstract: The structure of the proteoglycans from normal pig nucleus pulposus and relatively normal human annulus fibrosus and nucleus pulposus was investigated in detail and the results were compared with the current structural model of proteoglycans of hyaline cartilage. Like proteoglycans of cartilage, those of intervertebral disc contain keratan sulphate and chondroitin sulphate attached to a protein core; they are able to aggregate to hyaluronic acid; the protein core likewise has three regions, one lacking glycosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 36 publications
1
44
0
1
Order By: Relevance
“…This observation validated that the negatively charged nature of the CEP results from charged groups on the glycosaminoglycan (GAG) molecules on the proteoglycans (PGs) in the extracellular matrix. Moreover, there are two primary types of disaccharides in IVD tissues contributing to FCD, including chondroitin sulfate (CS), which has two negative charges per disaccharide, and keratin sulfate (KS), which carries one charged per disaccharide 21,38,39 . Previous studies have shown that the ratio of KS to CS varies regionally through the human IVD 38,40 , however the GAG content essay in this study wasn’t able to determine the ratio of KS to CS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation validated that the negatively charged nature of the CEP results from charged groups on the glycosaminoglycan (GAG) molecules on the proteoglycans (PGs) in the extracellular matrix. Moreover, there are two primary types of disaccharides in IVD tissues contributing to FCD, including chondroitin sulfate (CS), which has two negative charges per disaccharide, and keratin sulfate (KS), which carries one charged per disaccharide 21,38,39 . Previous studies have shown that the ratio of KS to CS varies regionally through the human IVD 38,40 , however the GAG content essay in this study wasn’t able to determine the ratio of KS to CS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are two primary types of disaccharides in IVD tissues contributing to FCD, including chondroitin sulfate (CS), which has two negative charges per disaccharide, and keratin sulfate (KS), which carries one charged per disaccharide 21,38,39 . Previous studies have shown that the ratio of KS to CS varies regionally through the human IVD 38,40 , however the GAG content essay in this study wasn’t able to determine the ratio of KS to CS. It may explain the regional effect discrepancies between FCD and GAG content in the human CEP: significant regional FCD variations were revealed using the electrical conductivity method, with the lowest value in the lateral region, while no significant regional variation was found for GAG content measured using the biochemical assay.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PGs exist mostly as monomers that exhibit lesser tendency to aggregate via hyaluronic acid compared with articular cartilage (Buckwalter, et al, 1985, Buckwalter, et al, 1989, Stevens, et al, 1979). Their lengths are estimated to be 70% shorter than PGs from cartilage and 40% shorter than those from the AF (Buckwalter, et al, 1989), and have a relatively high keratan sulfate content (Melrose, et al, 2001, Stevens, et al, 1979). Together, these components of the ECM impart a fluidic nature to the NP that suggests an enhanced ability to generate and sustain hydrostatic pressure during disc loading.…”
Section: Nucleus Pulposusmentioning
confidence: 99%
“…Antigens used to determine reactivity in vitro included the following: Candida albicans (Hollister-Steir Laboratories, Toronto, Ontario, dialyzed against phosphate-buffered saline, pH 7.4); collagen prepared from bovine achilles tendon [Sigma; dissolved and denatured as described (8)], the synthetic polypeptides (Gly-Sar-Pro)n (Sar, sarcosine), mean molecular weight 15,500, (Gly-Pro)n, mean molecular weight 11,000, (Pro)n, mean molecular weight 37,000; type I and type II collagen isolated from lathrytic chicken embryos; and proteoglycan, prepared as described (15)(16)(17) (the type I and type II collagen as well as the proteoglycan were purified to homogeneity as determined by sodium dodecyl sulfate/polyacrylamide gel electrophoresis and were generous gifts of Robert Siegel).…”
Section: Methodsmentioning
confidence: 99%